La postmémoire dans le discours politique de Manuel Valls et Anne Hidalgo - Carole Viñals (Cahiers de Civilisation Espagnole Contemporaine)
Through two French political figures, Anne Hidalgo and Manuel Valls, we show how the memory of Spanish Republicans is brought up in political discourse. To do this, we begin by recalling the cultural hybridity of these two children from immigrants who also constitute examples of perfect integration into the French model. Both have developed a story, a storytelling, of their family origins which has helped to forge a political image for them. We then consider the political speeches on La Nueve by Anne Hidalgo and on the Rivesaltes camp by Manuel Valls. In both cases, there is an instrumentalization of the memory of the Spanish Republicans, through the promotion of general values ​​in the Prime Minister and through depoliticization in Hidalgo.